Gewinnglättung und Steuerung dezentraler Investitionsentscheidungen bei sich gegenseitig ausschließenden Investitionsprojekten - Christian Gaber (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2002)
This paper examines the provision of managerial investment incentives by an accounting based incentive scheme in a multiperiod agency setting in which an impatient manager has to choose between mutually exclusive investment projects. We study the properties of accounting rules that motivate an impatient manager to exert unobservable effort and to make optimal investment decisions. In this analysis, a realized cash flow constitutes a noisy signal that contains information about the unknown profitability of the investment project. By observing these signals a principal is able to revise his prior beliefs about the agents investment decision. The revision of the principals prior beliefs leads to a trade off between the provision of efficient investment incentives and intertemporalsharing of output.
urn:nbn:de:hebis:30-17994
Keywords: M41; G31; D82; 330; Investitionsentscheidung; Dezentrale Organisation; Gewinnermittlung; Anreizvertrag; Prinzipal-Agent-Theorie; Theorie